Lessons on Synthetic Bioarchitectures Interaction of Living Matter with Synthetic Structural Analogues - Ehmoser-Sinner, Eva-Kathrin (Learning Materials in Biosciences,, 2018)
This textbook discusses the new relationship between artificial, synthetic material and living matter, and presents defined examples of approaches aiming for the creation of artificial cells. It also offers insights into the world of synthetic biology from its origins to the present day, showing what is currently possible in this discipline. Furthermore, it examines the ethical concerns and potential threats posed by this new field. The textbook is based on a lecture of the same title, held for master's students at the University of Natural Resources and Life Sciences (BOKU), Vienna, and is primarily intended for students of synthetic biology, biotechnology and bioengineering. It is also of interest to research scientists from other disciplines wishing to learn more about the state of the art of synthetic biology and its future.